A Eu(III)-based metal organic framework: selective detection of Fe3+ ion and treatment activity on the mucosal damage. Issue 9 (1st August 2022) - Luo, Zhe; Yu, Lan; Yan, Zhi-Hui; Liu, Xin-Yao; Zheng, Yan; Tian, Hua
Abstract: A novel metal–organic framework based on luminescent Eu(III) [Eu(TCPB)(DMF)]·dioxane·0.5H2 O n has been assembled via 1, 3, 5-tris(4-carbonylphenyloxy)benzene (H3 TCPB), a tripodal ligand through utilizing the approaches of solvothermal and then it was characterized via the EA together with the diffraction of single crystal X-ray. Under ultraviolet excitation, the 5 D0 / 7 F2 transition of Eu 3+ ions have red emission corresponding to the uniform structures of Eu-MOFs. It is worth noting that complex 1 has been investigated as a sensor for the detection of Fe 3+ ions. The ELISA was employed for the determination of the TGF-β and IL-6 content released via gastric mucosal cells after the treatment of compound. The detection of the signaling pathway activation of NF-κB was conducted with real time RT-PCR in gastric mucosal cells.